Strengthening the health workforce and rolling out universal health coverage: the need for policy analysis - Adam D. Koon; Susannah H. Mayhew (Taylor & Francis Group, 2013)
This article opens a debate about how to think about moving forward with the emerging twin movements of human resources for health (HRH) and universal health coverage (UHC). There is sufficient evidence to warrant these movements, but actors and the policy process significantly affect which policies are adopted and how they are implemented. How exactly this occurs in low- and middle-income countries (LMICs) is not very well understood. Furthermore, it is not clear whether actors will mobilize for or against the emergent HRH and UHC agendas. Policy analysis should help illuminate potential strategies to account for multiple interests and divergent values in volatile stakeholder environments. We argue that not only should the movement for UHC be paired with current efforts to address the human resources crisis, but also, for both to succeed, we need to know more about how health policy works in LMICs.